CITES And The International Protection Of Biodiversity - Venkateswarlu, Rayudu; Mowleswari, G. Chandra; Lakshmi, B. Kanaka; Lakshmi, Prof V Vijay (South Eastern European Journal of Public Health, 2025)
The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) was established in 1973 to address the increasing impact of trade on the conservation of wild species. The trade, which affects hundreds of millions of species, is difficult to regulate due to the scale of illegal trade. CITES is crucial for conservation of wild species as it addresses the global decline in biodiversity. The Convention considers threatened species from two angles: those threatened with extinction and those not yet threatened. The appropriate trade regulations are adopted based on the threat level and the degree of protection. CITES is an economic instrument, not a spatial or biological criteria-based protection mechanism. It is a first-generation convention that operates on three appendices, listing species based on their threat to their survival. The authorisation or prohibition of trade depends on this classification. Appendix-I lists all species threatened with extinction that are or could be affected by trade, while Appendix II includes all species that could become threatened with extinction if trade in specimens of these species were not subject to strict regulation. Appendix III includes all species declared to be subject to regulation intended to prevent or restrict their exploitation and requiring the cooperation of other Parties for the control of trade. The effectiveness of CITES has been the subject of significant studies on its effectiveness and efficiency. However, the control of the effectiveness of the Convention cannot be conducted with regard to all species threatened with extinction, as it would be both reductive and inaccurate. The CITES system is largely based on scientific advice and information, with authorizations or refusals to export or import specimens based on scientific advice. Environmental assessments have occupied an increasingly important place in recent years, particularly through assessments of the impacts of existing or future trade in species. The unbridled development of international material devoted to the environment can lead to questions about the legal, political, and scientific links existing between CITES and other international instruments relating to the environment and their influence on the effectiveness of the Convention. External cooperation are an important factor of dynamism for CITES and its partners, and they also seem to avoid contradictions or conflicts between the provisions of primary or secondary law of CITES and other international conventions.